Compêndio para planejamento de campanha de vacinação anual contra a raiva de cães e gatos na zona urbana de municípios - Babboni, Selene Daniela [UNESP] (2015)
Rabies is still a concerning worldwide disease with almost 100% lethality to people and the dog acting as the main carrier. The most efficient proceeding to control the disease is when 75% of the dog population in one city is vaccinated, amount that contributes to the interruption of the disease epidemiological transmission cycle, and, by consequence, public health protection. The experience accumulated since 1968 in planning the annual vaccination campaign in dogs and cats in different cities from São Paulo state aimed the elaboration of the present compendium. Material and methods were described and analyzed under the thematic and operational aspects from areas of knowledge and undertaken as proceedings to allow sustaining to elaborate subsequential sectorial politics. The compendium development, thus, was sustained on these 47 years of annual vaccination campaign against rabies based mainly on the area characteristics and animal and human populational dynamics at the target cities detailing the operational proceedings needed so that the goal to vaccinate the animals be achieved in each city considering further the cultural and socioeconomic conditions of the areas from the vaccination campaign planning